A creep-resistant additively manufactured Al-Ce-Ni-Mn alloy. (1st April 2022) - Michi, Richard A.; Sisco, Kevin; Bahl, Sumit; Yang, Ying; Poplawsky, Jonathan D.; Allard, Lawrence F.; Dehoff, Ryan R.; Plotkowski, Alex; Shyam, Amit
Abstract: Existing additively manufactured aluminum alloys exhibit poor creep resistance due to coarsening of their strengthening phases and refined grain structures. In this paper, we report on a novel additively manufactured Al-10.5Ce-3.1Ni-1.2Mn wt.% alloy which displays excellent creep resistance relative to cast high-temperature aluminum alloys at 300–400 °C. The creep resistance of this alloy is attributed to a high volume fraction (∼35%) of submicron intermetallic strengthening phases which are coarsening-resistant for hundreds of hours at 350 °C. The results herein demonstrate that additive manufacturing provides opportunities for development of creep-resistant aluminum alloys that may be used in bulk form in the 250–400 °C temperature range. Pathways for further development of such alloys are identified. Graphical abstract: Image, graphical abstract